Avaliação da exposição ácida esofágica, da motilidade do esôfago e da junção esofagogástrica em pacientes asmáticos - Lima, Maria Josire Vitorino (2019)
INTRODUCTION: Asthma and gastroesophageal reflux (GER) are widespread and disposable causes. Gastroesophageal reflux disease (GERD) presents with typical symptoms of reflux, gastritis and eating and digestive disorders. Asthma has several phenotypic features, including recurrent exacerbations and recurrent episodes of upper respiratory tract infection. Approximately 77% of asthmatics report heartburn. Asthma may predispose to the appearance of GERD genes in order to alter physiological function, vagal dysfunction, alteration of diaphragmatic function (CD) by altering the physiological function of antireflux barrier (BA) components and increasing the pressure of the sphincter effect. esophageal disease (LES) due to asthma treatment itself OBJECTIVE: Response to acid rush, esophageal motility and gastric esophageal junction (JEG) motility in asthmatic patients. METHODS: Twenty-six healthy, asymptomatic volunteers with a mean age of 35 ± 19.8 years were studied, 14 female and 12 male; 31 asthmatics with GERD, with a mean age of 46.2 ± 2.1 years, 29 female and 2 male. The riders performed clinical evaluation, anthropometric measurements, manovacuometry, high resolution esophageal manometry (MAR) and 24-hour pH monitoring, spirometry and inspiratory maneuvers with resistive loads of 12, 24, and10,75±48 cmH2O. RESULTS: Results of the healthy and asmatic groups, only age (p<0,004) and height (p<0.001) of the statistically significant results. Asthma symptoms (GINA) were positively correlated with predicted FEV1, mean control and mean standard, 1.84±1.77 and FEV1 mean standard deviation, respectively, 2,53±0,46. (r= 0,575) e (p=0,001). DS-JEG during a resting dive, no group had mean and standard deviation values, 3.98±0.78, and no asthmatic group had mean and standard deviation values, respectively, 3,36±1.04 with that of (p=0.018). Statistically significant. The diaphragm displacement time (DT-JEG) in the healthy group showed higher values in mean and standard deviation, respectively, 13.32 ± 5.43 and in the asthmatic group, it presented lower values in mean and standard deviation, respectively, 10.75 ± 2.48 with the value of (p = 0.032). Statistically significant. CONCLUSION: GERD symptoms are not correlated with the levels of asthma control (GINA) nor with asthma control by (ACQ7), nor with the forced expiratory volume in the predicted first second (FEV1), except with the predicted FEV1 that was positively associated asthma control (GINA), r=0,576 e p=0,001. In MAR (EGJ-Pmed) breathing at rest, correlated with levels of asthma control (GINA), r = 0.448 and p = 0.021, CI-EGJ load of 12 cmH2O, correlated with asthma control by (ACQ7), r = 0.443 and p = 0.023. Regarding acid exposure, the variable d% D of the fraction of time with reflux distal canal lying, correlated with asthma control by ACQ7), r = -0.376 and p = 0.036, and eight variables correlated with levels of asthma control (GINA).